Paths of life : American Indians of the Southwest and northern Mexico - Sheridan, Thomas E.; Parezo, Nancy J. (University of Arizona Press, 1996)
This book looks at history and culture of fifteen Native American groups in Arizona and northern Mexico, including: Navajos, Western Apaches, Hualapais, Yavapis, Havasupais, Yaquis, O'odham. Tarahumaras, Seris, Colorado River Yumans, and Hopis.